Color image encryption using chaotic-based cryptosystem - Mamat A.R.; Mohamed M.A.; Abidin A.F.A.; Mohamed R.R.; Sambas A.; Rusyn V.; Lisnichuk A.Ye.; Markovych B.M. (Lviv Polytechnic National University, 2025)
This paper presents research on a proposed project involving image encryption using a chaotic-based cryptosystem. The purpose is to create an image encryption environment with additional features derived from chaos theory. This cryptosystem applies the element of uncertainty and sensitivity to initial conditions. The encryption uses a symmetric key; generating a key is based on a chaotic map ? a nonlinear mathematical function that exhibits uncertainty and randomness based on initial values. Any change in the initial conditions affects the function?s outcome. Furthermore, this encryption aims to create a secure image-sharing environment over a public network, as image or text data can be intercepted or eavesdropped on by unauthorized users. A comparison based on image histogram analysis, pixel changes between the original and encrypted images, and encryption and decryption calculations were performed, demonstrating that the plain image differs from the encrypted image. ? 2024 Lviv Polytechnic National University.